ANALISIS LAPORAN ARUS KAS PEMERINTAH DAERAH (STUDI EMPIRIS DI PEMERINTAH KOTA MADIUN) - Hedi Pandowo; Ahmad Kudhori (Politeknik Negeri Malang, 2017)
This research was conducted with the aim to know the growth of cash flow that existed in the Cash Flow Statement in Madiun city government during 2012-2106. By creating a Cash Flow Statement, it will know the real cash movement from the beginning of the year to the end of the year, otherwise it can be known how much cash is used, for what cash is used for one operational year. This research is quantitative descriptive by using municipal government of Madiun as its object, especially in Badan Pengelola Keuangan dan Aset Daerah (BPKAD) as the agency that manage the assets of local government and preparing financial report. The data used is secondary data obtained from the official website of Madiun city government as well as data taken directly from the office of BPKAD. In this study obtained the result that overall growth of cash flow in 2012-2016 of operating activities, investment activities and financing activities show the financial performance both from the government of Madiun City. And from the free cash flow analysis results obtained during 2012 -2016 there is substantial free cash flow, so that with a large free cash flow indicates that local governments have surplus cash that can be used to supplement the reserve fund, pay off the local debt or invest in the form of equity participation